Manufacturing method of AMB ceramic copper-clad plate
By introducing rare earth element cerium and composite interface materials into the ceramic copper clad plate, and adopting metal activated layer materials and unique process steps, the defects of traditional ceramic copper clad plates in the bonding of copper and ceramics are solved, significantly improving the binding performance and production efficiency.
Patent Information
- Application Number
- CN202510035976.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-09
AI Technical Summary
Traditional ceramic copper clad plates have defects in the combination of copper and ceramics. High-temperature operation consumes high energy and can easily lead to deterioration of ceramic performance and unstable bonding interface, which limits the performance improvement and miniaturization of electronic equipment.
The AMB ceramic copper clad plate production method is used to significantly enhance the bonding performance of copper and ceramics by adding rare earth element cerium to aluminum nitride ceramics, using composite interface materials and metal activation layer materials, and using unique process steps such as plasma cleaning, pulsed laser deposition, ion beam assisted deposition and microwave smelting, etc.
It significantly enhances the bonding performance of ceramics and copper layers, improves the overall quality and production efficiency of the product, reduces the process temperature requirements, and solves the problems of ceramic performance deterioration and instability in the bonding interface in traditional methods.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of electronic material manufacturing, and in particular to a method for manufacturing an AMB ceramic copper-clad plate. Background Art
[0002] With the rapid development of electronic technology, the defects of traditional ceramic copper-clad laminates in the bonding of copper and ceramics have become increasingly prominent. The existing process often requires high-temperature operation, which not only consumes a lot of energy, but also easily causes problems such as ceramic performance degradation and unstable bonding interface, which seriously restricts the performance improvement and miniaturization of electronic devices. Therefore, it is urgent to develop new production methods to overcome these shortcomings.
[0003] The patent with publication number CN117042340A discloses a method for pattern engraving of a ceramic copper-clad laminate, thereby obtaining a method for manufacturing a ceramic copper-clad laminate with better quality, comprising the following steps: a. material preparation: the ceramic layer and the copper layer are welded into a whole through a brazing layer; b. pattern engraving: a reserved copper layer is provided between the bottom of the processing groove and the brazing layer closest to the bottom of the processing groove, and the bottom of the reserved copper layer is a reserved brazing layer; c. chemical etching protection treatment: first, the outermost copper layer is protected by a photosensitive dry film; d. reserved copper layer treatment: the reserved copper layer is processed by a chemical copper etching method to obtain a bare reserved brazing layer, and after the processing is completed, the protective photosensitive dry film is removed; e. reserved brazing layer treatment: the above-mentioned exposed reserved brazing layer is etched away by a chemical etching method, and finally a bare ceramic layer is obtained.
[0004] This method not only protects the last exposed ceramic layer very well, but also can realize the processing of multi-layer ceramic copper clad laminates very well. However, the ceramic copper clad laminates prepared by this method have a lot of room for improvement in thermal conductivity, bonding strength and insulation performance. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for manufacturing an AMB ceramic copper-clad laminate, introduce new ceramic materials, composite interface materials, metal activation layer materials and unique processes, significantly enhance the bonding performance between copper and ceramics, reduce process temperature requirements, improve product overall quality and production efficiency, and provide innovative solutions for the field of electronic materials.
[0006] To achieve the above object, the technical solution adopted by the present invention is: A method for manufacturing an AMB ceramic copper-clad laminate, the specific steps are as follows: Step 1, material preparation: using aluminum nitride ceramics added with rare earth element cerium as the basic ceramic layer material; using zirconium powder and titanium nitride powder as raw materials to make a composite interface material; using copper, cobalt and gallium as raw materials to make a metal activation layer material; Step 2, ceramic substrate pretreatment: Use plasma to clean the cerium aluminum nitride ceramic sheet for 10-15 minutes to remove impurities, organic matter and oxide layer, and then vacuum dry at 120℃-150℃ for 1-2h to ensure that the ceramic sheet is clean and dry, providing a good base for subsequent processes; Step 3: Composite interface coating: Use pulsed laser deposition technology to coat the composite interface material film on the surface of the ceramic sheet for 20-30 minutes at a laser energy density of 2-4J / cm² and a pulse frequency of 10-15Hz at a suitable temperature; Step 4, metal activation layer deposition: using ion beam assisted deposition, 50-80keV ion beam energy, 10-15μA / cm² beam current density and 0.05-0.2μm / min deposition rate, to deposit a metal activation layer on the composite interface layer; Step 5: Copper layer bonding: Place the boron-treated oxygen-free copper sheet on the deposited activation layer ceramic sheet. -5 -1×10 -6 Pa ultra-high vacuum at 450℃-550℃ for 40-70 minutes; Step 6, post-treatment: After hot pressing, the ceramic copper clad laminate is first kept at 350℃-400℃ for 1-1.5h, then heated to 450℃-500℃ for 1.5-2h, and finally slowly cooled to room temperature for gradient annealing. After that, the copper layer is electrochemically polished for 3-5 minutes with a 3:1 mixture of phosphoric acid and sulfuric acid and a voltage of 2-3V to form an ultra-smooth surface.
[0007] Preferably, in step 1, the specific preparation method of the aluminum nitride ceramic added with the rare earth element cerium is as follows: Step 11: Accurately weigh the required mass of high-purity aluminum nitride powder, and calculate the exact mass of the cerium additive based on the predetermined total ceramic amount and the cerium addition ratio of 0.1%-0.5%; Step 12: The weighed aluminum nitride powder and cerium additive are placed in a ball mill of a planetary ball mill. The ball mill uses agate balls as grinding balls, and the ball-to-material ratio is set between 5:1 and 10:1. Anhydrous ethanol in an amount of 5% to 10% of the total mass of the powder is added to the ball mill as a dispersant, and then ball milling is performed; Step 13: After the ball milling is completed, the mixed powder in the ball mill is taken out and placed in a vacuum drying oven for drying. The drying temperature is set at 80°C-100°C, the vacuum degree is maintained at 0.05-0.1MPa, and the drying time is 6-10h to completely remove the dispersant in the powder; Step 14: The dried powder is sieved through a 200-400 mesh screen to obtain the cerium-containing aluminum nitride ceramic powder raw material.
[0008] Preferably, in step 1, the specific method for preparing the composite interface material using zirconium powder and titanium nitride powder as raw materials is: mixing submicron zirconium powder and titanium nitride powder in a mass ratio of 2:3-3:4, ball milling in a planetary ball mill at 400-600r / min for 15-20h, and adding 0.2%-0.4% of the total mass of PEG-b-PS dispersant to prevent agglomeration, and then mixing the obtained composite powder with 8%-12% of the total mass of aluminum phosphate binder to form a film.
[0009] Preferably, in the step 1, the specific method for preparing the metal activation layer material using copper, cobalt and gallium as raw materials is: prepare 65%-75% copper, 12%-18% cobalt, and 10%-15% gallium, and after microwave melting at 1100°C-1200°C for 1.5-2h, cast it into a 3-8μm thin sheet to obtain the metal activation layer.
[0010] Preferably, in step 2, the vacuum drying temperature is 120-150° C., and the vacuum drying time is 1-2 h.
[0011] Preferably, in step 3, the temperature when the composite interface material film is coated on the surface of the ceramic sheet by pulse laser deposition technology is 200° C.-300° C.
[0012] More preferably, the film made of the composite interface material has a thickness of 8-15 μm.
[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention significantly optimizes the sintering process of the ceramic by adding 0.1%-0.5% of rare earth cerium (Ce) to the aluminum nitride ceramic. The introduction of cerium promotes the refinement of grains and makes the ceramic microstructure more uniform and dense. This directly enhances the mechanical toughness of the ceramic, enabling it to better withstand the mechanical stress during subsequent processing and use. For example, in a thermal cycle or mechanical shock environment, the probability of cracks and breakage in cerium-containing aluminum nitride ceramics is greatly reduced compared to unmodified ceramics. At the same time, thermal stability is also improved, maintaining good structural integrity and performance stability in a high temperature environment, effectively preventing material failure caused by thermal stress, and thus providing a more reliable basic support layer for the entire ceramic copper clad laminate.
[0014] 2. The composite interface material prepared by mixing submicron zirconium powder and titanium nitride powder in a mass ratio of 2:3-3:4 in the present invention performs well in the subsequent bonding process with ceramics and copper layers. After long-term ball milling in a planetary ball mill and the action of a dispersant, the raw materials are evenly mixed and agglomeration is effectively suppressed. The film mixed with an aluminum phosphate binder has good formability and adhesion. After being deposited on the ceramic surface, it can form a tight chemical bond with the ceramic. At the same time, its own metal phase component enhances its affinity with the copper layer, effectively improving the bonding interface performance between copper and ceramics, significantly improving the bonding strength, reducing the risk of interface stratification, and enhancing the overall reliability of the product. 3. The metal activation layer material of the present invention, which is composed of 65%-75% copper, 12%-18% cobalt and 10%-15% gallium, plays a key activation role between the ceramic and the copper layer after microwave melting and rapid solidification treatment. Microwave melting allows the three metals to be quickly and evenly mixed at a relatively low temperature (1100°C-1200°C), shortening the melting time and reducing the segregation of metal components. Rapid solidification technology refines the grain structure and improves material properties. After being deposited on the composite interface layer, cobalt and gallium elements can promote the chemical reaction between the metal activation layer and ceramics and copper at a lower temperature, forming a stable metallurgical bond, effectively reducing the process temperature required for the bonding of copper and ceramics, while enhancing the bonding strength and stability, and improving product quality and production efficiency. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0016] The inventors of this application discovered during the research that rare earth elements have unique electronic structures and chemical activities, and can play a dual role as grain boundary migration inhibitors and grain growth promoters during the ceramic sintering process. Cerium was selected because it has a significant effect on improving ceramic performance and is relatively cost-effective. By adding a small amount of cerium, the interaction with the aluminum nitride matrix at high temperature is utilized to change the grain growth dynamics, achieve grain refinement and structural optimization, and thus improve the comprehensive performance of the ceramic, meeting the requirements of the ceramic copper-clad laminate for high strength and high stability of the ceramic base.
[0017] In addition, zirconium and titanium nitride have good chemical activity and mechanical properties respectively, and the combination of the two can produce a synergistic effect. Submicron powder is selected to increase the specific surface area, improve the reaction activity and bonding effect. The ball milling process ensures uniform mixing, and the binder ensures the quality of the film. By carefully designing the raw material ratio and preparation process, it aims to construct a transition layer that can not only closely bond with the ceramic but also promote metallurgical bonding with the copper layer, solve the problem of poor bonding between copper and ceramic in traditional processes, and improve the interface bonding quality and stability.
[0018] The inventors also found that based on the study of the chemical properties and interactions of metal elements, copper was selected as the main component to ensure good conductivity, and cobalt and gallium were added to utilize their unique advantages in promoting metal-ceramic bonding reactions. The use of microwave melting and rapid solidification technology is to overcome the shortcomings of traditional melting processes, achieve efficient and high-quality material preparation, meet the needs of achieving strong bonding at lower temperatures, reduce the negative impact of high temperatures on material properties, and promote the development of ceramic copper clad laminate manufacturing processes towards low temperature and high efficiency.
[0019] The present invention is further disclosed below in conjunction with embodiments: Example 1 In this embodiment, a method for manufacturing an AMB ceramic copper clad laminate is provided, and the specific steps are as follows: Step 1, material preparation: using aluminum nitride ceramics added with rare earth element cerium as the basic ceramic layer material; using zirconium powder and titanium nitride powder as raw materials to make a composite interface material; using copper, cobalt and gallium as raw materials to make a metal activation layer material; The specific preparation method of aluminum nitride ceramics added with rare earth element cerium is as follows: Step 11: Accurately weigh the required mass of high-purity aluminum nitride powder, and calculate the exact mass of the cerium additive based on the predetermined total ceramic amount and the cerium addition ratio of 0.1%; Step 12: The weighed aluminum nitride powder and cerium additive are placed in a ball mill of a planetary ball mill. The ball mill uses agate balls as grinding balls, and the ball-to-material ratio is set to 5:1. Anhydrous ethanol of 5% of the total mass of the powder is added to the ball mill as a dispersant, and then ball milling is performed; Step 13: After the ball milling is completed, the mixed powder in the ball mill is taken out and placed in a vacuum drying oven for drying. The drying temperature is set at 80°C, the vacuum degree is maintained at 0.05MPa, and the drying time is 6h to completely remove the dispersant in the powder; Step 14: the dried powder is sieved through a 400-mesh sieve to obtain the cerium-containing aluminum nitride ceramic powder raw material; The specific method for preparing the composite interface material using zirconium powder and titanium nitride powder as raw materials is as follows: submicron zirconium powder and titanium nitride powder are mixed in a mass ratio of 2:3, ball milled in a planetary ball mill at 400 / min for 15 hours, and 0.2% of the total mass of PEG-b-PS dispersant is added to prevent agglomeration, and then the obtained composite powder is mixed with 8% of the total mass of aluminum phosphate binder to prepare a film with a thickness of 8 μm; Furthermore, the specific method of making the metal activation layer material using copper, cobalt and gallium as raw materials is as follows: preparing 75% copper, 12% cobalt and 13% gallium, melting them by microwave at 1200°C for 1.5h, and casting them into 3-8μm thin sheets to obtain the metal activation layer; Step 2, ceramic substrate pretreatment: Use plasma to clean the cerium aluminum nitride ceramic sheet for 15 minutes to remove impurities, organic matter and oxide layer, and then vacuum dry it at 120°C for 2 hours to ensure that the ceramic sheet is clean and dry, providing a good base for subsequent processes; Step 3: Composite interface coating: Use pulsed laser deposition technology to coat the composite interface material film on the surface of the ceramic sheet for 20 minutes at a laser energy density of 2J / cm² and a pulse frequency of 15Hz, and the temperature is controlled at 300℃; Step 4, metal activation layer deposition: ion beam assisted deposition, 50keV ion beam energy, 15μA / cm² beam current density and 0.2μm / min deposition rate, to deposit a metal activation layer on the composite interface layer; Step 5: Copper layer bonding: Place the boron-treated oxygen-free copper sheet on the deposited activation layer ceramic sheet. -5 Pa ultra-high vacuum 550℃ hot pressing bonding for 50 minutes; Step 6, post-treatment: After hot pressing, the ceramic copper-clad laminate is first kept at 350°C for 1 hour, then heated to 500°C for 2 hours, and finally slowly cooled to room temperature for gradient annealing to effectively eliminate internal stress. After that, the copper layer is electrochemically polished with a 3:1 mixture of phosphoric acid and sulfuric acid and a voltage of 3V for 5 minutes to form an ultra-smooth surface.
[0020] Example 2 In this embodiment, a method for manufacturing an AMB ceramic copper clad laminate is provided, and the specific steps are as follows: Step 1, material preparation: using aluminum nitride ceramics added with rare earth element cerium as the basic ceramic layer material; using zirconium powder and titanium nitride powder as raw materials to make a composite interface material; using copper, cobalt and gallium as raw materials to make a metal activation layer material; The specific preparation method of aluminum nitride ceramics added with rare earth element cerium is as follows: Step 11: Accurately weigh the required mass of high-purity aluminum nitride powder, and calculate the exact mass of the cerium additive based on the predetermined total ceramic amount and the cerium addition ratio of 0.3%; Step 12: The weighed aluminum nitride powder and cerium additive are placed in a ball mill of a planetary ball mill. The ball mill uses agate balls as grinding balls, and the ball-to-material ratio is set to 7:1. Anhydrous ethanol in an amount of 7% of the total mass of the powder is added to the ball mill as a dispersant, and then ball milling is performed; Step 13: After the ball milling is completed, the mixed powder in the ball mill is taken out and placed in a vacuum drying oven for drying. The drying temperature is set at 80°C, the vacuum degree is maintained at 0.1MPa, and the drying time is 10h to completely remove the dispersant in the powder; Step 14: the dried powder is sieved through a 300-mesh sieve to obtain the cerium-containing aluminum nitride ceramic powder raw material; The specific method for preparing the composite interface material using zirconium powder and titanium nitride powder as raw materials is as follows: submicron zirconium powder and titanium nitride powder are mixed in a mass ratio of 3:4, ball milled in a planetary ball mill at 600 r / min for 20 h, and 0.4% of the total mass of PEG-b-PS dispersant is added to prevent agglomeration, and then the obtained composite powder is mixed with 10% of the total mass of aluminum phosphate binder to prepare a film with a thickness of 10 μm; Furthermore, the specific method for preparing the metal activation layer material using copper, cobalt and gallium as raw materials is as follows: preparing 70% copper, 18% cobalt and 12% gallium, melting them by microwave at 1200°C for 2h, and casting them into 5μm thin sheets to obtain the metal activation layer; Step 2: Pretreatment of ceramic substrate: Use plasma to clean the cerium aluminum nitride ceramic sheet for 15 minutes to remove impurities, organic matter and oxide layer, and then vacuum dry it at 150°C for 2 hours to ensure that the ceramic sheet is clean and dry, providing a good substrate for subsequent processes; Step 3: Composite interface coating: Use pulsed laser deposition technology to coat the composite interface material film on the surface of the ceramic sheet for 30 minutes at a laser energy density of 3J / cm² and a pulse frequency of 15Hz, and the temperature is controlled at 300℃; Step 4, metal activation layer deposition: ion beam assisted deposition, 80keV ion beam energy, 15μA / cm² beam current density and 0.2μm / min deposition rate, to deposit a metal activation layer on the composite interface layer; Step 5: Copper layer bonding: Place the boron-treated oxygen-free copper sheet on the deposited activation layer ceramic sheet. -5 Pa ultra-high vacuum at 550 ° C for 60 minutes; Step 6, post-treatment: After hot pressing, the ceramic copper-clad laminate is first kept at 400°C for 1.5 hours, then heated to 500°C for 2 hours, and finally slowly cooled to room temperature for gradient annealing to effectively eliminate internal stress. After that, the copper layer is electrochemically polished with a 3:1 mixture of phosphoric acid and sulfuric acid at a voltage of 3V for 5 minutes to form an ultra-smooth surface.
[0021] Example 3 In this embodiment, a method for manufacturing an AMB ceramic copper clad laminate is provided, and the specific steps are as follows: Step 1, material preparation: using aluminum nitride ceramics added with rare earth element cerium as the basic ceramic layer material; using zirconium powder and titanium nitride powder as raw materials to make a composite interface material; using copper, cobalt and gallium as raw materials to make a metal activation layer material; The specific preparation method of aluminum nitride ceramics added with rare earth element cerium is as follows: Step 11: Accurately weigh the required mass of high-purity aluminum nitride powder, and calculate the exact mass of the cerium additive based on the predetermined total ceramic amount and the cerium addition ratio of 0.5%; Step 12: The weighed aluminum nitride powder and cerium additive are placed in a ball mill of a planetary ball mill. The ball mill uses agate balls as grinding balls, and the ball-to-material ratio is set to 10:1. Anhydrous ethanol of 10% of the total mass of the powder is added to the ball mill as a dispersant, and then ball milling is performed; Step 13: After the ball milling is completed, the mixed powder in the ball mill is taken out and placed in a vacuum drying oven for drying. The drying temperature is set at 100°C, the vacuum degree is maintained at 0.1MPa, and the drying time is 10h to completely remove the dispersant in the powder; Step 14: the dried powder is sieved through a 400-mesh sieve to obtain the cerium-containing aluminum nitride ceramic powder raw material; The specific method for preparing the composite interface material using zirconium powder and titanium nitride powder as raw materials is as follows: submicron zirconium powder and titanium nitride powder are mixed in a mass ratio of 3:4, ball milled in a planetary ball mill at 600 r / min for 20 h, and 0.4% of the total mass of PEG-b-PS dispersant is added to prevent agglomeration, and then the obtained composite powder is mixed with 12% of the total mass of aluminum phosphate binder to prepare a film with a thickness of 15 μm; Furthermore, the specific method for preparing the metal activation layer material using copper, cobalt and gallium as raw materials is as follows: preparing 69% copper, 18% cobalt and 13% gallium, melting them by microwave at 1200°C for 2h, and casting them into 8μm thin sheets to obtain the metal activation layer; Step 2: Pretreatment of ceramic substrate: Use plasma to clean the cerium aluminum nitride ceramic sheet for 15 minutes to remove impurities, organic matter and oxide layer, and then vacuum dry it at 150°C for 2 hours to ensure that the ceramic sheet is clean and dry, providing a good substrate for subsequent processes; Step 3: Composite interface coating: Use pulsed laser deposition technology to coat the composite interface material film on the surface of the ceramic sheet for 30 minutes at a laser energy density of 4J / cm² and a pulse frequency of 15Hz, and the temperature is controlled at 300℃; Step 4, metal activation layer deposition: ion beam assisted deposition, 80keV ion beam energy, 10-15μA / cm² beam current density and 0.2μm / min deposition rate, deposit a metal activation layer on the composite interface layer; Step 5: Copper layer bonding: Place the boron-treated oxygen-free copper sheet on the deposited activation layer ceramic sheet. -5 Pa ultra-high vacuum at 550 ° C for 70 minutes; Step 6, post-treatment: After hot pressing, the ceramic copper-clad laminate is first kept at 350°C for 1 hour, then heated to 500°C for 2 hours, and finally slowly cooled to room temperature for gradient annealing to effectively eliminate internal stress. After that, the copper layer is electrochemically polished with a 3:1 mixture of phosphoric acid and sulfuric acid and a voltage of 3V for 5 minutes to form an ultra-smooth surface.
[0022] Comparative Example 1 The ceramic copper-clad laminate was made by conventional high-temperature brazing without any new materials and processes. Copper and ceramic were brazed at 850°C with a silver-based brazing filler metal to prepare samples, and the conventional materials and processes were compared with those disclosed in the present invention.
[0023] Comparative Example 2 Compared with Example 1, this example omits the step of preparing the composite interface material, and the rest are the same. Samples are prepared to explore the effect of the composite interface material on the bonding performance.
[0024] Comparative Example 3 Compared with Example 1, no metal activation layer material is used, copper and ceramic are directly hot pressed to prepare samples, and the effect of the metal activation layer is analyzed.
[0025] For the samples in Examples 1-3 and Comparative Examples 1-3, performance tests were performed in the following manner: in accordance with GB / T5270-2020, a universal material testing machine was used to perform a tensile test on the bonding strength of the material; with reference to GB / T3651-2008, a laser flash method was used to measure the thermal conductivity; in accordance with GB / T1410-2006, a high resistance meter was used to measure the insulation resistance of the ceramic layer to test the insulation performance of the material. The test results are as follows: It can be seen from the above table that the insulation resistance performance of the samples in Examples 1-3 is extremely outstanding. For example, the insulation resistance of Example 3 is as high as 1.6×10¹²Ω・cm. Such a high insulation resistance value fully demonstrates that these samples can effectively prevent current leakage in the application scenarios of electronic equipment, and provide a solid guarantee for the stable operation of electronic equipment. It fully meets the strict requirements of electronic equipment for insulation performance, and effectively reflects the good insulation properties of the AMB ceramic copper clad laminate prepared by the present invention.
[0026] In terms of bonding strength, the bonding strengths of Examples 1-3 are all within the relatively high range of 55.6-56.7MPa. In contrast, the bonding strength of the sample made by conventional high-temperature brazing in Comparative Example 1 is only 32.5MPa; the bonding strength of the sample in Comparative Example 2 without the composite interface material step is 41.4MPa; the bonding strength of the sample in Comparative Example 3 without the metal activation layer material is 45.7MPa; obviously, the bonding strength of the embodiments of the present invention far exceeds that of each comparative example, which strongly proves the outstanding effect of optimizing processes and materials in improving bonding performance.
[0027] In terms of thermal conductivity, the samples in the examples also show significant advantages. The thermal conductivity of Example 1 is 280W / (m・K), Example 2 is 279W / (m・K), and Example 3 is 273W / (m・K); in contrast, the thermal conductivity of the samples in Comparative Examples 1-3 made by traditional processes is only between 228W / (m・K) and 257W / (m・K), which fully demonstrates that the new method of the present invention has obvious advantages in maintaining high thermal conductivity and can better meet the needs of electronic equipment in terms of heat dissipation.
[0028] Based on the test results of key indicators such as bonding strength, thermal conductivity and insulation performance, the optimized AMB ceramic copper clad laminate production method has excellent performance in all aspects. It has successfully overcome a series of difficulties existing in traditional processes such as insufficient bonding strength, limited thermal conductivity and difficult to ensure insulation performance, providing a reliable and innovative technical path for the development of the electronic materials industry. It is expected to be widely used and promoted in the field of electronic materials in the future, and promote the entire industry to develop in the direction of higher performance and higher efficiency.
[0029] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for manufacturing an AMB ceramic copper-clad laminate, characterized in that: The specific steps are as follows: Step 1, material preparation: using aluminum nitride ceramics added with rare earth element cerium as the basic ceramic layer material; using zirconium powder and titanium nitride powder as raw materials to make a composite interface material; using copper, cobalt and gallium as raw materials to make a metal activation layer material; Step 2, ceramic substrate pretreatment: Use plasma to clean the cerium aluminum nitride ceramic sheet for 10-15 minutes to remove impurities, organic matter and oxide layer, and then vacuum dry at 120℃-150℃ for 1-2h to ensure that the ceramic sheet is clean and dry, providing a good base for subsequent processes; Step 3: Composite interface coating: Use pulsed laser deposition technology to coat the composite interface material film on the surface of the ceramic sheet for 20-30 minutes at a laser energy density of 2-4J / cm² and a pulse frequency of 10-15Hz at a suitable temperature; Step 4, metal activation layer deposition: using ion beam assisted deposition, 50-80keV ion beam energy, 10-15μA / cm² beam current density and 0.05-0.2μm / min deposition rate, to deposit a metal activation layer on the composite interface layer; Step 5: Copper layer bonding: Place the boron-treated oxygen-free copper sheet on the deposited activation layer ceramic sheet. -5 -1×10 -6 Pa ultra-high vacuum at 450℃-550℃ for 40-70 minutes; Step 6, post-treatment: After hot pressing, the ceramic copper clad laminate is first kept at 350℃-400℃ for 1-1.5h, then heated to 450℃-500℃ for 1.5-2h, and finally slowly cooled to room temperature for gradient annealing. After that, the copper layer is electrochemically polished for 3-5 minutes with a 3:1 mixture of phosphoric acid and sulfuric acid and a voltage of 2-3V to form an ultra-smooth surface.
2. The method for manufacturing an AMB ceramic copper-clad laminate according to claim 1, wherein: In the step 1, the specific preparation method of the aluminum nitride ceramic added with the rare earth element cerium is as follows: Step 11: Accurately weigh the required mass of high-purity aluminum nitride powder, and calculate the exact mass of the cerium additive based on the predetermined total ceramic amount and the cerium addition ratio of 0.1%-0.5%; Step 12: The weighed aluminum nitride powder and cerium additive are placed in a ball mill of a planetary ball mill. The ball mill uses agate balls as grinding balls, and the ball-to-material ratio is set between 5:1 and 10:
1. Anhydrous ethanol in an amount of 5% to 10% of the total mass of the powder is added to the ball mill as a dispersant, and then ball milling is performed; Step 13: After the ball milling is completed, the mixed powder in the ball mill is taken out and placed in a vacuum drying oven for drying. The drying temperature is set at 80°C-100°C, the vacuum degree is maintained at 0.05-0.1MPa, and the drying time is 6-10h to completely remove the dispersant in the powder; Step 14: The dried powder is sieved through a 200-400 mesh screen to obtain the cerium-containing aluminum nitride ceramic powder raw material.
3. The method for manufacturing the AMB ceramic copper-clad laminate according to claim 1, characterized in that: In the step 1, the specific method for preparing the composite interface material using zirconium powder and titanium nitride powder as raw materials is: submicron zirconium powder and titanium nitride powder are mixed in a mass ratio of 2:3-3:4, ball milled in a planetary ball mill at 400-600 r / min for 15-20 hours, and 0.2%-0.4% of the total mass of PEG-b-PS dispersant is added to prevent agglomeration, and then the obtained composite powder is mixed with 8%-12% of the total mass of aluminum phosphate binder to form a film.
4. The method for manufacturing an AMB ceramic copper-clad laminate according to claim 1, wherein: In the step 1, the specific method for preparing the metal activation layer material using copper, cobalt and gallium as raw materials is: prepare 65%-75% copper, 12%-18% cobalt, and 10%-15% gallium, and after microwave melting at 1100° C.-1200° C. for 1.5-2 hours, cast it into a 3-8 μm thin sheet to obtain the metal activation layer.
5. The method for manufacturing the AMB ceramic copper-clad laminate according to claim 1, characterized in that: In the step 2, the vacuum drying temperature is 120-150° C., and the vacuum drying time is 1-2 h.
6. The method for manufacturing the AMB ceramic copper-clad laminate according to claim 1, characterized in that: In the step 3, the temperature is 200° C.-300° C. when the composite interface material film is coated on the surface of the ceramic sheet by pulse laser deposition technology.
7. The method for manufacturing the AMB ceramic copper-clad laminate according to claim 3, characterized in that: The thickness of the film made of the composite interface material is 8-15 μm.
Citation Information
Patent Citations
Ceramic copper-clad plate manufacturing method
CN117042340A
Preparation method of aluminum nitride ceramic copper-clad plate
CN108033810A
AMB silicon nitride ceramic copper-coated sheet and preparation method thereof
CN116133269A
Metal-Ceramic Substrate
US20120045657A1